Exploratory window‐of‐opportunity trial to investigate the tumor pharmacokinetics/pharmacodynamics of the IAP antagonist Debio 1143 in patients with head and neck cancer. Issue 1 (11th November 2021) - Gomez‐Roca, Carlos; Even, Caroline; Le Tourneau, Christophe; Basté, Neus; Delord, Jean‐Pierre; Sarini, Jerome; Vergez, Sebastien; Temam, Stephane; Hoffmann, Caroline; Rochaix, Philippe; Borcoman, Edith; Gavillet, Bruno; et al.
Abstract: Inhibitor of apoptosis proteins (IAPs) regulate apoptosis and modulate NF‐κB signaling thereby driving expression of genes involved in immune/inflammatory responses. The orally available IAP antagonist Debio 1143 has potential to enhance tumor response to chemoradiotherapy and/or immunotherapy. Patients with pre‐operative squamous cell carcinomas of the head and neck (SCCHN) received: Debio 1143 monotherapy (200 mg/day [D]1–15 +/‐ 2); Debio 1143 (200 mg/day D1–15 +/‐ 2) plus cisplatin (40 mg/m 2 D 1 and 8); cisplatin alone (40 mg/m 2 D 1 and 8; EudraCT: 2014‐004655‐31). Pharmacokinetic/pharmacodynamic effects were assessed in plasma and resected tumors. Primary end point; effect of Debio 1143 on cellular IAP‐1 (cIAP‐1). Levels of cIAP‐1/‐2, X‐linked inhibitor of apoptosis protein (XIAP), tumor infiltrating lymphocytes (TILs), including CD8+ T cells, programmed cell death protein 1 (PD‐1), PD‐ligand 1 (PD‐L1), and gene expression were also analyzed. Twenty‐three of 26 patients completed treatment. In the Debio 1143 monotherapy cohort ( n  = 13), mean tumor concentrations of Debio 1143 were 18‐fold (maximum 55.2‐fold) greater than in plasma, exceeding the half‐maximal inhibitory concentration for cIAPs and XIAP by 100 to 1000‐fold, with significant engagement/degradation of cIAP‐1 ( p  < 0.05). Overall, levels of CD8+ TILs, PD‐1, and PD‐L1 positive immune cells increased significantly ( p  < 0.05) following Debio 1143 treatment. Changes were observed in the expression of genes related to NF‐κB signaling. Treatments were well‐tolerated. Debio 1143 penetrated SCCHN tumors, engaged cIAP‐1, and induced immune inflammatory changes in the tumor microenvironment. Based on the mode of action demonstrated here and in previous studies, these data support future combinations of Debio 1143 with immune‐checkpoint agents.